TRANSFORMATION OF GOVERNMENT BOND YIELDS DURING THE DEBT CRISIS - Yakubovskiy , S.; Hryhorian , R.; Derenko , V. (The actual problems of regional economy development, 2020)
The article analyzes the yield on government bonds, both long-term and short-term, the countries most affected by the debt crisis, namely Greece, Italy, Portugal, as well as the countries that have benefited most from the circumstances, namely Germany and France. There was an increase in the yield of two types of government bonds (maturity of 10 years and 1 year) for all analyzed countries (except Germany and France) during the debt crisis since late 2009. The peak yield on government bonds in Southern Europe fell in 2011. During the debt crisis, German government bonds benefited and, as a result, the yields on German and French government bonds declined. In the following years, the yield on government bonds of Southern Europe, as well as Germany and France declined. The article also constructs vector autoregressions (VARs) of interdependence between different types of government bond yields, their difference and government debt, government budget, GDP of the analyzed countries. It was found that in Germany, the relationship of these indicators was not observed. However, there is a strong unilateral dependence of government debt on the yield on long-term and short-term government bonds, as well as government debt on the yield difference. In France, there is an interdependence between government debt and the yield of short-term bonds. It is worth noting the strong dependence of long-term profitability on government debt, as well as the impact of government debt on the difference. In Greece, there is a dependence of the yield on long-term government bonds, as well as the difference between all three indicators. In Portugal, there is a strong relationship between the yield on short-term bonds and government debt, as well as between the government budget and the difference. In Italy, there is an uneven relationship between the yield on the two types and GDP, and the yield on long-term and short-term government bonds depends on the government budget. There is also a strong impact of government debt on the difference in yields on government bonds.